PREVALENCE OF INSULIN RESISTANCE IN TYPE-2 DIABETIC PATIENTS - Shah, Nazir; Ullah, Aman; Attaullah, Salma (Journal of Postgraduate Medical Institute, 2011)
Objective: To determine the prevalence of insulin resistance in patients of type-2 diabetes mellitus in population of NWFP, using the National Cholesterol Education Program Adult Treatment Panel-III definition of insulin resistance,(modified for Asians) Material and Methods: This analytical study was performed in Fauji Foundation Hospital and Hayatabad Medical Complex Peshawar. Two hundred and eighty patients of type-2 diabetes mellitus of age 30 or above were included from the hospital OPD and wards. Those patients, who were having high waist circumference because of reasons other than abdominal fat like pregnancy, ascites, abdominal tumors etc, were excluded from the study. Patients with severe infection and inflammatory conditions were also excluded. All the patients were examined for waist circumference and blood pressure, and investigated for fasting blood sugar, triglyceride and S HDL. The above mentioned criteria was applied to know whether a patients is insulin resistant or not. Results: Two hundred & eighty patients of Type-2 diabetes mellitus were collected randomly from the hospital OPD. Ninety-five were males and 185 were females. Seventy eight percent 78% (n=219) of the patients were fulfilling the criteria for metabolic syndrome (insulin resistance). The prevalence of metabolic syndrome was almost equal in male 77% (n=73) and females 79% (n=146). The ratio of central obesity was more in the females 78% (n=144) than in the males 70% (n=67). The total prevalence of hypertension was 71% (n=199). The ratio of hypertension was more in the male 75% (n=71) than in the female 67% (n=124). Conclusion: Insulin resistance is very common in type-2 diabetes mellitus. Treating the insulin resistance with insulin sensitizing drugs will prove beneficial regarding the diabetic control and prevention of its macro vascular complications.